Insecticide Resistance Profiles and Synergism of Field Aedes aegypti from Indonesia. - Christina Natalina Silalahi; Wu-Chun Tu; Niann-Tai Chang; G Veera Singham; Intan Ahmad; Kok-Boon Neoh (Public Library of Science (PLoS), 2022)
Information on the insecticide resistance profiles of Aedes aegypti in Indonesia is fragmentary because of the lack of wide-area insecticide resistance surveillance. We collected Ae. aegypti from 32 districts and regencies in 27 Indonesian provinces and used WHO bioassays to evaluate their resistance to deltamethrin, permethrin, bendiocarb, and pirimiphos-methyl. To determine the possible resistance mechanisms of Ae. aegypti, synergism tests were conducted using piperonyl butoxide (PBO) and S,S,S-tributylphosphorotrithioates (DEF). The Ae. aegypti from all locations exhibited various levels of resistance to pyrethroids. Their resistance ratio (RR50) to permethrin and deltamethrin ranged from 4.08× to 127× and from 4.37× to 72.20×, respectively. In contrast with the findings of other studies, most strains from the highly urbanized cities on the island of Java (i.e., Banten, Jakarta, Bandung, Semarang, Yogyakarta, and Surabaya) exhibited low to moderate resistance to pyrethroids. By contrast, the strains collected from the less populated Kalimantan region exhibited very high resistance to pyrethroids. The possible reasons are discussed herein. Low levels of resistance to bendiocarb (RR50, 1.24-6.46×) and pirimiphos-methyl (RR50, 1.01-2.70×) were observed in all tested strains, regardless of locality. PBO and DEF synergists significantly increased the susceptibility of Ae. aegypti to permethrin and deltamethrin and reduced their resistance ratio to less than 16×. The synergism tests suggested the major involvement of cytochrome P450 monooxygenases and esterases in conferring pyrethroid resistance. On the basis of our results, we proposed a 6-month rotation of insecticides (deltamethrin + synergists ➝ bendiocarb ➝ permethrin + synergists ➝ pirimiphos-methyl) and the use of an insecticide mixture containing pyrethroid and pyrimiphos-methyl to control Ae. aegypti populations and overcome the challenge of widespread Ae. aegypti resistance to pyrethroid in Indonesia.